2002
DOI: 10.1176/appi.ps.53.9.1159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residents' Depression, Sleep, and Demand for Medication on Benzodiazepine Use in Nursing Homes

Abstract: Efforts to improve benzodiazepine use in nursing homes must address the need for better assessment and management of depression, sleep, pain, and residents' demand for these medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Older adults metabolize drugs slower than younger adults; thus, medications such as hypnotics that are commonly prescribed to older adults are particularly cumulative and dangerous (Ancoli-Israel & Kripke, 1991). Many older adults with dementia, particularly those who reside in nursing homes, are prescribed antipsychotics, antidepressants, benzodiazepines, and nonbenzodiazepine sedative hypnotics (Simpson, Richards, Enderlin, O'Sullivan, & Koehn, 2006;Svarstad & Mount, 2002). These medications, however, may have negative side effects, including sleep disturbances.…”
Section: Medicationsmentioning
confidence: 99%
“…Older adults metabolize drugs slower than younger adults; thus, medications such as hypnotics that are commonly prescribed to older adults are particularly cumulative and dangerous (Ancoli-Israel & Kripke, 1991). Many older adults with dementia, particularly those who reside in nursing homes, are prescribed antipsychotics, antidepressants, benzodiazepines, and nonbenzodiazepine sedative hypnotics (Simpson, Richards, Enderlin, O'Sullivan, & Koehn, 2006;Svarstad & Mount, 2002). These medications, however, may have negative side effects, including sleep disturbances.…”
Section: Medicationsmentioning
confidence: 99%
“…The most prescribed psychotropic drugs are anxiolytics and hypnotics (Garolera et al, 2001;Sorensen et al, 2001). Such drugs tend to be used for periods exceeding the recommended course of treatment (Offerhaus, 1997;Svarstad and Mount, 2002). Dosages are sometimes too high: a study showed that 40% of residents in long-term care facilities received on average 1.5 times the recommended dose of psychotropic medication, irrespective of the family (Schmidt et al, 1998b).…”
Section: Problemmentioning
confidence: 99%
“…Antipsychotics are indicated to treat schizophrenia and other psychotic disorders, but nursing homes have been criticized previously for using them as chemical restraints to treat behavior problems 12,13. Similarly, benzodiazepines, which can be effective in treating anxiety disorders and insomnia in the elderly, may be used inappropriately to treat nursing home residents with depression or mild behavior problems 14. Although these medications are effective when used appropriately, prior research demonstrates substantial misuse of these drugs in nursing homes and the potential for serious side effects (e.g., sedation, falls, delirium, and even death) in frail older residents who commonly have cognitive impairment and substantial comorbidity 1524.…”
mentioning
confidence: 99%
“…Our work builds on previous research that has examined the use of psychotropic drugs among nursing home residents7,14,2628 and includes benzodiazepines, which have been relatively understudied, when compared with antipsychotics. Furthermore, we include many resident and facility traits not previously examined and use a large nationally representative dataset of U.S. facilities and their residents.…”
mentioning
confidence: 99%